The Role Of Information Abundance In The Paramedic’s Ability To Quickly Assess Cases And Accurately Determine Their Needs During Accidents - Abdullah Abed Abdullah Althagafi,; Khalid Atiah Althagafi,; Rashdan Zham Atiuah Alzabaliy,; Asim Obead Alsulme,; Mohammed Sanad Smran Allehaiby,; Faisal Mohammed Alaaqil Kazim,; Khalifa Mohammed Khalifa Bin Rasheed, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The study aimed to identify the role of information abundance in the ability of paramedics to assess cases quickly and accurately determine their needs during emergencies This was achieved through a questionnaire focused on the importance of information, the necessity of obtaining information, and the significance of the information abundance recorded by the paramedics, as well as the extent to which this information can save the lives of the injured The study revealed a set of results indicating that information abundance assists paramedics in writing accurate and correct reports, which facilitate proper diagnosis of the condition and prepare it for appropriate treatment The study recommends the need to enhance paramedics' awareness of the proper and correct methods for recording patient data